2014
DOI: 10.1038/cdd.2014.49
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Keap1 activates BH3-only proteins Bim and PUMA during hepatocyte lipoapoptosis

Abstract: Non-alcoholic steatohepatitis is characterized by hepatic steatosis, elevated levels of circulating free fatty acids (FFA) and hepatocyte lipoapoptosis. This lipoapoptosis requires increased JNK phosphorylation and activation of the pro-apoptotic BH3-only proteins Bim and PUMA. Kelch-like ECH-associated protein (Keap)-1 is a BTB/Kelch protein that can regulate the expression of Bcl-2 protein and control apoptotic cell death. Yet, the role of Keap1 in hepatocyte lipotoxicity is unclear. Here we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…However, the interaction of DmKeap1 with DmAtg8a is interesting, both because DmKeap1 appears to recognize a different binding surface in DmAtg8a than Ref(2)P and other LIR-containing proteins and because the interaction might have an important role for DmAtg8a-mediated autophagic degradation of DmKeap1 during Drosophila development. Recent studies show mammalian Keap1 to be degraded by autophagy under nutritional starvation and oxidative stress in a p62-dependent manner (34,76), whereas degradation of mammalian Keap1 by basal autophagy has not been clearly demonstrated. Consistent with this, we observed no degradation of DmKeap1 by basal autophagy in Drosophila, but DmKeap1 was degraded under programmed autophagy during Drosophila development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction of DmKeap1 with DmAtg8a is interesting, both because DmKeap1 appears to recognize a different binding surface in DmAtg8a than Ref(2)P and other LIR-containing proteins and because the interaction might have an important role for DmAtg8a-mediated autophagic degradation of DmKeap1 during Drosophila development. Recent studies show mammalian Keap1 to be degraded by autophagy under nutritional starvation and oxidative stress in a p62-dependent manner (34,76), whereas degradation of mammalian Keap1 by basal autophagy has not been clearly demonstrated. Consistent with this, we observed no degradation of DmKeap1 by basal autophagy in Drosophila, but DmKeap1 was degraded under programmed autophagy during Drosophila development.…”
Section: Discussionmentioning
confidence: 99%
“…2C) (Rada et al, 2011(Rada et al, , 2012. Moreover, KEAP1 interacts with other proteins that also contain the high-affinity binding motif ETGE (Hast et al, 2013), such as Bcl-2 and IKKb (Kim et al, 2010a;Cazanave et al, 2014). Therefore, some results obtained from KEAP1-deficient cells may not necessarily be related to NRF2 activation.…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 98%
“…Table 3 compiles recent patents addressing these small molecules. Although these compounds are very promising, it is still needed to demonstrate that they are selective for the KEAP1/NRF2 interaction, because KEAP1 also targets at least Bcl2 and IKK (Kim et al, 2010a;Hast et al, 2013;Cazanave et al, 2014).…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…3 Therefore, in our recent study we evaluated the role of KEAP1 in hepatocyte lipotoxicity. 4 In both primary and transformed liver cells, we observed that sFFA-induced toxicity was associated with degradation of KEAP1, in part through autophagy in a sequestrosome (SQSTM)1/p62-dependent manner. We also identified that loss of Keap1 induced spontaneous liver cell death and further increased hepatocyte susceptibility to a lipotoxic insult.…”
mentioning
confidence: 82%
“…This effect was associated with increased activation of c-Jun NH2 terminal kinase (JNK) in an NRF2-independent manner and upregulation of protein levels of Bcl-2-interacting mediator (BIM) and p53 upregulated modulator of apoptosis (PUMA), 2 proapoptotic BH3-only proteins that induce hepatocyte cell death. 4 Autophagy is often observed in dying cells as it is activated by oxidative stress. Although it is mostly considered a prosurvival pathway it can also contribute to cell death, especially if the process relates to lysosomal dysfunction and the activation of caspase-8, which are both implicated in lipotoxicity.…”
mentioning
confidence: 99%